Optimalisasi Proses Bioremediasi Secara In Situ Pada Lahan Tercemar Pestisida Kelompok Mankozeb - Yohanes, Setiyo; Utama, Made S; Tika, Wayan; Gunadnya, IBP. (Jurnal Teknik Industri, 2011)
Compost as an organic fertilizer could improve the physical, chemical, and biological characteristics of the soil in aÂ certain way so that soil mineral was available for plant. The special aim of this research was to optimize the bioremediation process for degradation of pesticide residues at Bedugul Agro-tourism so that organic farming system will be sustainable. Based on C/N, and pH, it could be concluded that better solution for bioremediation of pesticide residue problem was by giving mixed-compost in horticulture cultivation. Deviation of pH in bioremediation process was 0.22, and pH in-situ bioremediation process was between 6.9 and 7.12 or neutral pH. In this condition micro-organism would be effective in degrading pesticide residue. Bioremediation process on pesticide residue of Ditane M-45 at horticulture cultivation deploy with 1.2 g/l/20 m2, 2.4 g/l/20 m2, and 3.6 g/l/20 m2 spraying dosages took place perfectly, which was showed by parameters on development of micro-organism population and the amount of pesticide residues. Pesticide residue of each spraying dosages was 0.25â€“1.7% at 35 days or this values were under 0.003 ppm.